Tributyltin-resistant bacteria from contaminated surface sediment - Abubakar, Abdussamad; Mustafa, Muskhazli; Wan Johari, Wan Lutfi; Mohamat Yusuff, Ferdius @ Ferdaus; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Resistance to tributyltin (TBT) was examined in pure bacteria cultures isolated from TBT-polluted sediments. We defined a TBT-resistant bacterium as one which grows in a TBT concentration above the reported concentration at the sampling site (Kong Kong Laut), which was less than 1000μg/l. More than 15 pure colonies of bacteria were isolated which are mostly Gram negative and more than 80% percent of these isolates are possible TBT-degrading bacteria due to their ability to resist TBT concentration of up to 1000μg/l. All TBT-resistant bacteria are potential TBT degrading bacteria but may not degrade the TBT. However, TBT degrading bacteria must be TBT resistant bacteria. These TBT-resistant bacteria were also examined for their biodegradability and they shows capability of degrading TBT, suggesting that these microorganism can utilize the carbon source in the pollutant. This study has successfully shown that these bacteria isolated from Kong Kong Laut are potential TBT-degrading bacteria and this also paves a major pathway for sustainable remediation solution.